2007
DOI: 10.1111/j.1471-4159.2007.04596.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic second‐by‐second measures of l‐glutamate in the central nervous system of freely moving rats

Abstract: L-glutamate (Glu) is the main excitatory neurotransmitter in the central nervous system (CNS) and is associated with motor behavior and sensory perception. While microdialysis methods have been used to record tonic levels of Glu, little is known about the more rapid changes in Glu signals that may be observed in awake rats. We have reported acute recording methods using enzyme-based microelectrode arrays (MEA) with fast response time and low detection levels of Glu in anesthetized animals with minimal interfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
196
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 127 publications
(214 citation statements)
references
References 28 publications
11
196
0
Order By: Relevance
“…anesthetized animal studies, microdialysis shows evidence of tissue disruption of at least 220-250 mm away from the probe (Borland et al, 2005), whereas the MEA showed evidence of some neuroinflammation only 50-100 mm away in a chronic study following 8 weeks in vivo (Rutherford et al, 2007). The temporal resolution of our MEA is an order of magnitude faster than the most sophisticated microdialysis techniques designed for measurement of aminoacid neurotransmitters (Kennedy et al, 2002).…”
Section: Discussionmentioning
confidence: 85%
“…anesthetized animal studies, microdialysis shows evidence of tissue disruption of at least 220-250 mm away from the probe (Borland et al, 2005), whereas the MEA showed evidence of some neuroinflammation only 50-100 mm away in a chronic study following 8 weeks in vivo (Rutherford et al, 2007). The temporal resolution of our MEA is an order of magnitude faster than the most sophisticated microdialysis techniques designed for measurement of aminoacid neurotransmitters (Kennedy et al, 2002).…”
Section: Discussionmentioning
confidence: 85%
“…Although electroactive amino acids could be detected at microelectrode Pt surfaces without selective coatings (e.g., mPD), such exclusion coatings are used for in vivo experiments to minimize or eliminate interfering agents. 25,26 16 The mPD effectively blocked potentially interfering electroactive species including amino acids. The published resting levels of amino acids range from 1 to 10 μM for most amino acids and 41 μM for glutamine.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The MEA paddle was modified for use in freely moving animals as extensively described in previous literature (Hascup et al, 2008;Rutherford et al, 2007, Hascup et al, 2006. Briefly, the pedestal was the portion of the system that was chronically implanted on the rat's head and contained the MEA.…”
Section: Ceramic Mea Preparationmentioning
confidence: 99%
“…MEA implantation has been extensively described in previous literature (Hascup et al, 2010(Hascup et al, , 2009Rutherford et al, 2007). The MEA pedal assembly was implanted in the right PFC (MEA tip coordinates: AP: + 3.2 mm; ML: 0.8 mm, DV: À5.0 mm vs bregma), with the incisor bar set so that the skull was level (À2.3 mm), which was based on the atlas of Paxinos and Watson (1998).…”
Section: Mea Implantationmentioning
confidence: 99%
See 1 more Smart Citation